Analysis of Measuring Student Satisfaction with Teacher Performance Assessment Using the Naive Bayes Model - Irma Yurni; Arief Rahman; Zahratul Fitri (Multica Science and Technology, 2024)
Naive Bayes model analysis to evaluate teacher quality based on the grades given by students with the variables of communication, mastery of material, teacher involvement, and teaching methods have an important role in determining student satisfaction assessments. The analysis results from the naive Bayes model show that student satisfaction tends to be higher for teachers who have good communication skills, strong mastery of the material, active involvement in the teaching and learning process, and the use of effective and innovative teaching methods. Therefore, to improve the quality of education, it is necessary to increase teacher competence in these four variables. In addition, the application of Naive Bayes model analysis can be an effective tool for identifying students who need improvement and development in analyzing student satisfaction. Naïve Bayes model analysis is used to predict the probability of student satisfaction based on the attributes involved. The results of the research show that analyzing and classifying student satisfaction assessments with good accuracy using the Naive Bayes model makes it easy to estimate the probability of satisfaction based on the attributes given. The results of research using the naive Bayes model with a probability of yes 0.0576 with a likelihood of yes and no getting a value of 0.6 while the probability of no is 0.0384 with a value of 0.4. for Normalization results 1 and Probability Value YES > Probability Value NO, Then Student Satisfaction with Teacher Performance is Satisfied with Teacher Performance.